Location is (still) everything the surprising influence of the real world on how we search, shop, and sell in the virtual one - Bell, David R. (2014)
"Conventional wisdom holds that the Internet makes the world flat and reduces friction, erasing the impact of the physical world on our buying habits. But Wharton professor and marketing expert David R. Bell argues that the way we use the Internet is largely shaped by the physical world that we inhabit. Anyone can go online and buy a pair of pants...but the likelihood that we would do so depends to a significant degree on where we live. The presence of stores nearby, trendy and friendly neighbors, and local sales taxes play a large role in the decision-making process when it comes to buying online. Location Is (Still) Everything is for anyone who wants to understand the patterns underlying how and why we use the Internet to shop, sell, and search, including entrepreneurs, students, and investors. This book is not only about Internet trends and innovations, but also about fundamental human behavior and the role that the Internet plays in our daily lives"..
Keywords: BUSINESS & ECONOMICS / Commercial Policy; BUSINESS & ECONOMICS / Consumer Behavior; Gesellschaft; Psychologie; Wirtschaft; Electronic commerce -- Social aspects; Electronic commerce -- Psychological aspects; Internet marketing; Consumer behavior; Consumers -- Psychology; Consumption (Economics); Online-Marketing; Verbraucherverhalten